The Effect of Mortar Grade and Thickness on the Impact Resistance of Ferrocement Slab - Muda Z.C.; Syamsir A.; Mustapha K.N.; Sulleman S.; Beddu S.; Thiruchelvam S.; Ismail F.B.; Usman F.; Mohd Kamal N.L.; Alam M.A.; Birima A.H.; Itam Z.; et al. (Institute of Physics Publishing, 2023)
Concrete slabs; Cracks; Drops; Mesh generation; Reinforced concrete; Reinforcement; Drop weight impact; Linear correlation; Low impacts; Mesh reinforcement; Mesh spacing; Projectile tests; Slab thickness; Steel balls; Mortar; cement; concrete; cracking; impact; loading; mortar; spacing; steel structure; weight